Management Information Systems / Organization and Technology: Third Edition - Laudon Jane Price; Laudon Kenneth C (Macmillan Publishing Company, 1994)
Organizational Foundations of Information Systems, The Challenge of Information Systems, Examples of Information Systems, Strategic Information Systems, Information Systems and Organizations, Information and Management and Decision Making, Technical Foundations of Information Systems, Computers and Information Processing, Information Systems Software, Managing Data Resources, Telecommunications The New Information Architecture, Building Information Systems: Contemporary Approaches, Redesigning the Organization with Information Systems, Alternative Systems-Building Methods, Ensuring Quality with Information Systems, System Success and Failure: Implementation, Management and Organizational Support Systems, Knowledge and Information Work Systems, Enhancing Management Decision Making, Artificial Intelligence, Managing Contemporarary Information Systems, Controlling Information Systems, Managing International Information Systems, Ethical and Social Issues in Information Systems, Index.
Organizational Foundations of Information Systems, The Challenge of Information Systems, Examples of Information Systems, Strategic Information Systems, Information Systems and Organizations, Information and Management and Decision Making, Technical Foundations of Information Systems, Computers and Information Processing, Information Systems Software, Managing Data Resources, Telecommunications The New Information Architecture, Building Information Systems: Contemporary Approaches, Redesigning the Organization with Information Systems, Alternative Systems-Building Methods, Ensuring Quality with Information Systems, System Success and Failure: Implementation, Management and Organizational Support Systems, Knowledge and Information Work Systems, Enhancing Management Decision Making, Artificial Intelligence, Managing Contemporarary Information Systems, Controlling Information Systems, Managing International Information Systems, Ethical and Social Issues in Information Systems, Index.